Survivability of acanthamoeba strains isolated from clinical and environmental specimens during axenization - Nurul Farhana Jufri,; Anisah Nordin,; Mohamed Kamel Abd Ghani,; Yusof Suboh,; Noraina Abd Rahim, (Penerbit UKM, 2011)
Acanthamoeba is a free living protozoa that can cause keratitis and granulomatous amoebic encephalitis. Physiological characteristics of this amoeba are found to have a medical importance in which it can be related to the pathogenicity potential of the organism. This study was carried out to investigate the physiological characteristics of survivability during axenization. Six Acanthamoeba strains from three clinical isolates (HSB 1, HKL 48 and HKL 95) and three environmental isolates (PHS 2, PHS 11 and PHS 15) were used in this study. Axenization test was done by treating cysts with hydrochloric acid (3%) and Page saline containing Gentamicin (100 μg/ml). Cysts were then cultured into PYG enrich media, incubated at 30oC and the presence and proliferation of trophozoites of Acanthamoeba were observed. This study showed that PHS 15, HSB 1, HKL 48 and HKL 95 could be axenized but they have poor proliferation rate in PYG enrich media. The result showed that the difference between both clinical and environmental isolates was observed in two strains; PHS 2 and PHS 11. This indicates that there is a possibility that the physiological traits of strains from both isolates are the same and strains from the environment are able to show the pathogenic potential and capable of causing infection to human.